THE EFFECT OF STORE ATMOSPHERE AND EXPERIENTIAL MARKETING ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION AT SALEJOURN CAFE AND SPACE PADANG: PENGARUH STORE ATMOSPHERE DAN EXPERIENTIAL MARKETING TERHADAP LOYALITAS PELANGGAN YANG DIMEDIASI OLEH KEPUASAN PELANGGAN DI SALEJOURN CAFE AND SPACE PADANG - Fanisa Nadya Putri; Fitria Ridhaningsih (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to determine the influence of store atmosphere and experiential marketing on customer loyalty mediated by customer satisfaction at Salejourn Cafe and Space Padang. In this study, 110 samples were used which were then processed using the Partial Least Square (PLS) application. The results of this study show that: (1) Store Atmosphere has a positive effect on customer loyalty at Salejourn Cafe and Space Padang (2) Experiential Marketing has a positive effect on customer loyalty at Salejourn Cafe and Space Padang (3) Store Atmosphere has a positive effect on customer satisfaction at Salejourn Cafe and Space Padang (4) Experiential Marketing has a positive effect on customer satisfaction at Salejourn Cafe and Space Padang (5) Customer Satisfaction has a positive effect on customer loyalty at Salejourn Cafe and Space Padang (6) Customer satisfaction mediates the relationship between store atmosphere and experiential marketing on customer loyalty at Salejourn Cafe and Space Padang